Open Learning: Systems and Problems in Post-Secondary Education/Distance Education: A Survey and Bibliography. - Elton, L. R. B. (Journal of Higher Education)
The article reviews the books "Open Learning: Systems and Problems in Post-Secondary Education," by Norman MacKenzie and "Distance Education: A Survey and Bibliography," by Börje Holmberg.